2018
DOI: 10.1186/s13012-018-0835-5
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish version of the Normalization Process Theory Measure S-NoMAD: translation, adaptation, and pilot testing

Abstract: BackgroundThe original British instrument the Normalization Process Theory Measure (NoMAD) is based on the four core constructs of the Normalization Process Theory: Coherence, Cognitive Participation, Collective Action, and Reflexive Monitoring. They represent ways of thinking about implementation and are focused on how interventions can become part of everyday practice.AimTo translate and adapt the original NoMAD into the Swedish version S-NoMAD and to evaluate its psychometric properties based on a pilot tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 21 publications
2
46
0
Order By: Relevance
“…Of the 372 manuscripts screened, 58 were eligible for inclusion and data were extracted. Fifty-eight manuscripts [76][77][78][79]. No studies of intruments measuring implementation cost were identified (see Fig.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 372 manuscripts screened, 58 were eligible for inclusion and data were extracted. Fifty-eight manuscripts [76][77][78][79]. No studies of intruments measuring implementation cost were identified (see Fig.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Acceptability: consumer = 10 [23,37,39,41,42,44,51,52,57,59], provider = 27 [24-36, 38, 40, 43, 45-50, 53-56, 58] Appropriateness: consumer = 3 [61][62][63], provider = 3 [46,60,64], both consumer and provider = 1 [65] Adoption: consumer = 1 [66], provider = 3 [67][68][69] Feasibility: provider = 4 [46,70,71,80] Penetration: organisation = 4 [72][73][74][75] Sustainability: provider = 2 [76,77], organisation = 2 [78,79] Methodological quality Table 1 presents the global COSMIN scores for reliability, validity and responsiveness, and rank orders the instruments by descending reliability scores. Detailed COSMIN scores for individual measurement properties are presented in Additional file 3.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…The measurement instruments used to assess implementation success or related outcomes (i.e. NoMAD, ORIC, and implementation costs measure) are relatively new, though promising [ 42 44 , 51 ]. Experience of the field to use these validated measures is low, and therefore, the interpretation might not be as straightforward compared to well-established instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The NoMAD is a self-report instrument measuring the degree of normalization by focusing on four constructs as defined by the Normalization Process Theory [ 35 ]: coherence, cognitive participation, collective action, and reflexive monitoring. The NoMAD shows high internal consistency and has been validated in heterogeneous samples across languages and settings [ 42 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The NPT has been widely used to analyse the implementation of complex health care interventions and has proven to be useful and beneficial [17]. Although it is a new approach to assess an implementation process using NoMAD, the instrument has been tested in a Swedish version [32].…”
Section: Strengths and Weaknessesmentioning
confidence: 99%